The Use of Zeolit and Activated Carbon on Packing System of Corydoras aenus - E. Supriyono; E. Supendi; K. Nirmala (Jurnal Akuakultur Indonesia)
Problem frequently found by Indonesian exporter in sending ornamental fish including Corydoras aenus to overseas is the low survival rate that caused by decrease in water quality during transportation.  Suitable and efficient packing technology is very needed to send live fish for long time transportation.  Two third of packing plastic volume was filled by oxygen, and Corydoras aenus 20 fish/pack.  Packing plastic was placed into styrofoam and ice was added to maintain at low temperature.  Zeolit and activated carbon was cover up by cloth and then placed into the pack.  Dosage treatment of zeolit and activated carbon was 20 gram zeolit, 15 gram zeolit and 5 gram activated carbon, 10 gram zeolit and 10 gram activated carbon, 5 gram zeolit and 15 gram activated carbon, 20 gram activated carbon, and no added zeolit and no activated carbon as control.  Fish condition was observed every 6 hours, while water quality measurement was performed every 24 hours for 120 hours.  The results of study showed that adding 20 gram zeolit without activated carbon in closed packing system of Corydoras aenus in 20oC could maintained in lower concentration of total nitrogen ammonia and unionized ammonia (NH3), reached of 7.83±0.13 mg/l and 0.046±0.003 mg/l, respectively.  The level of total nitrogen ammonia and unionized ammonia were relatively lower compared to mix of zeolit and activated carbon, and only activated carbon.  Survival rate of fish by this treatment was 100%, higher than other treatment (85-95%).